Moral Development of Children during the COVID-19 Pandemic - Nia Anggri Noveni; Bagus Rizqy Yudhya Putra; Mellyna Putri Utami; Putri Rahmawati; Maharani Susilowati; Aidul Akbar Diawara; Anisha Alyadini (UM Purwokerto Press, 2021)
The Covid-19 pandemic requires people to implement social distancing (activity restrictions) to anticipate the spread of Covid-19. This study aims to determine the moral development of children during the Covid-19 pandemic and to determine the role of adults in the formation of children's moral development during the pandemic. The subjects of this study amounted to 104 people who are parents or siblings who are in the same house with children in Pandemic. This study uses a quantitative approach with survey methods and data collection techniques used are questionnaires through Google Form. The survey results show that only 75% of parents or siblings of children make regulations related to social distancing, while 25% do not make regulations related to social distancing. Basically, the attitude shown by adults will have a big influence on the children moral’s reasoning about social distancing. In addition, children aged 0-5 years have not obeyed the rules made, but children aged above 5-10 years will begin to obey the rules. Meanwhile, at the age of 9 to more than 10 years, children begin to consider the purpose and consequences of social distancing rules that have been made by adults.